Drug policy and the public good - Babor, Thomas (Oxford : Oxford University Press, 2010)
Written by an international group of addiction scientists, this book is intended to improve the links between addiction science and drug policy. It presents the accumulated scientific knowledge on drug use research that has a direct relevance to the development of drug policy at local, national and international levels.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Drug control; Substance abuse -- Government policy